Spleen Morphological Features Under Experimental Model of Multiple Organ Failure and Stem Cell Application - Likhodiievskyi, Volodymyr V.; Korsak, Alina V.; Irodov, Dmytro M.; Chaikovskyi, Yuri B.; Kordium, Vitalii A.; Olefir, Serhii S.; Zabila, Anna O.; Kovalchuk, Maria V.; Ruban, Tetyana A.; Shuvalova, Nadiia S. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 064–068